Enhanced hole transport in InGaN/GaN multiple quantum well light-emitting diodes with a p-type doped quantum barrier - Ji, Yun (2013)
We study hole transport behavior of InGaN/GaN light-emitting diodes with the dual wavelength emission method. It is found that at low injection levels, light emission is mainly from quantum wells near p-GaN, indicating that hole transport depth is limited in the active region. Emission from deeper wells only occurs under high current injection. However, with Mg-doped quantum barriers, holes penetrate deeper within the active region even under low injection, increasing the radiative recombination. Moreover, the improved hole transport leads to reduced forward voltage and enhanced light generation. This is also verified by numerical analysis of hole distribution and energy band structure.